Environment as a Political Object: Contributions from Political Culture for Building a Post-normal Political Science in Latin America - Vizcarra Castillo, Sofía Isabel (2025)
We discuss, based on a narrative theoretical review, the basis for the development of post-normal political culture studies for a better understanding of the environment as a political object in Latin America. To this end, we conduct a historical reconstruction of approaches to the environment as a political object and its arrival in the discipline of political science. Despite the absence a of a "green" subfield in the behaviourist tradition of political science, the environment has been the object of various political culture studies, mainly from the Global North. We review these studies and recognise their theoretical and methodological contributions but point out that they can only explain the phenomenon in Latin America to a limited extent. Likewise, we show how the characteristics of Latin American hybrid political culture and the lines of development of State-society relations in the region are explanatory elements to understand what we could call the paradox of the ecological imagination in the region.